Effects of a glyphosate-based herbicide on the development and biochemical biomarkers of the freshwater copepod Notodiaptomus carteri (Lowndes, 1934) - Fantón, Noelia Isabel (2020)
In this work we analyzed the effects of Sulfosato Touchdown®, a glyphosate-based herbicide, on the ontogenic development and biochemical markers of the freshwater copepod Notodiaptomus carteri. A 30-days life-cycle experiment was carried out with three different glyphosate concentrations (0, 0.38, and 0.81 mg L−1) to analyze the developmental time from nauplii to adult copepods and their individual growth. An additional 10-days experiment with the same glyphosate concentrations was designed to evaluate the energy reserves (glycogen, proteins and lipids) and the activity of three antioxidant enzymes, superoxide dismutase (SOD), catalase, and glutathione-S-transferase (GST) in adult copepods, separately for females and males. We found that the lowest glyphosate concentration increased the nauplii and total development time. The highest glyphosate concentration prevented copepods from reaching the adult stage, inhibited the growth of the first copepodite stage and increased the GST and SOD activity in adult females. According to our results, the presence of this herbicide in freshwater systems could impose a risk in the ecological role of copepods in nature. This study will contribute to propose the Notodiaptomus genus as model specie for monitoring purposes in the Neotropical aquatic systems.